Three Realistic Principles for Nurturing Ethical Prosocial Behavior - Plante, Thomas (My University, 2025)
The world is in trouble with numerous significant challenges to life and society such as climate change, divisive politics, economic disparity, war, racism and discrimination, and violence. At the core of these issues is human behavior and in particular, ethical decision making. The purpose of this reflection is to underscore three practical principles to encourage more prosocial behavior by (a) embracing the reality of egoism, (b) finding ways to merge egoism with the common good, and (c) socially engineer ethical behavior that benefits society. Considering ethical decision making and nurturing prosocial behavior in a realistic manner provides at least some hope for relieving the many difficulties that our society faces.
Keywords: Egoism; common good; ethical behavior; prosocial behavior; ethics